Rakhitis: Tinjauan Pustaka - Helmi Ismunandar; Rani Himayani; Maula Al Farisi (CV. Jasa Sukses Abadi, 2021)
Vitamin D and calcium are important nutrients in bones. Bone growth and mineralization are dependent on the availability of adequate calcium and phosphate. Due to the lack of mineralization in the bone plates it causes rickets. Rickets is the most common bone disease worldwide and became known in 1650’s when it first appeared in Europe. Rickets can have a profound impact on the health, growth and development of infant’s, children’s and adolescent’s which can result in death or persistence to adult. Rickets is a metabolic disease of the bones, that is often associated with vitamin D deficiency and decreased circulating calcium storage, mainly due to a lack of bone capacity to absorb the calcium. Usually people with rickets have a short stature and have joint disorders. There are several types of rickets, such as rickets type-1 and type-2 that depend on vitamin D (but in type-2 rickets involves a genetic disorder related to the FGF23 gene), renal rickets due to decreased of kidney function, rickets hypocalcemia caused by deficiency of calcium, and hypophosphatemic rickets caused by deficiency of phosphate. Rickets can be diagnosed based on history, physical examination, radiological examination and biochemical tests.